(3efXheI GdSjQI GdfHhjIs - (3GdMfaj, GdMdHj, GdeOGQj, HQgGf GdOjf, EHQGgje Hf eUWai Hf EHQGgje, (B1190 (3g`s ((3cJH NGfg eMeO QGZH HGTGs)
(3ChdgG (B:s
(3CHOC HGSe Gddg GdQMef Ke GdQMje efRd GdaQbGf hMeO ef YdefG Yde GdSjQ hUdhGJg Ydi NjQ GdHTQ hUMHg fLhe GdGgJOGA hBdg GdQLhe ddCYOGA hHYO aGdSjQ Ph JSjjQ ddabg hGdMOjK hGdJaSjQ s
(3BNQgG (B:s
(3MLI ehJ GHfg SQi Ydi NGdO GdCTYQj hKfj GdHLdj aj SO CSGeI GaJQG WdjMI YfSj SLGM eaJQi GdjeGeI eQV fbd ddQajb GdCYdi Udi Ydjg Gddg MjK MdGs
(3JHUQI GdYfhGf (B:s
(3GdefXheI GdMdHjI aj GdSjQI GdfHhjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1/74s
(3eYLe GdeDdajf (B1/73s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs